2018
DOI: 10.17222/mit.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and analysis of the wear properties of friction-stir-welded AA7075-T6 and A384.0-T6 dissimilar aluminium alloys of butt joints

Abstract: The wear is one of the main issues in friction-stir welding (FSW) of dissimilar aluminium alloys. Two dissimilar metals welded with FSW have different mechanical, metallurgical and chemical properties compared to the parent materials. Therefore, the wear resistance is an important property in an FSW process. In this research, AA7075-T6 and A384.0-T6 aluminium alloys with a thickness of 6.35 mm were selected and a design matrix was developed to produce FSW welds using the MINITAB-17 software. Friction-stir-weld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Karuppannan Anganan et al [11] analysed the wear attributes of stir welded AA 7075 and A384 (Both in T6 condition). Experimentation revealed that higher order of wear is observed for A384 T6 and lower trend is observed for the later.…”
Section: Introductionmentioning
confidence: 99%
“…Karuppannan Anganan et al [11] analysed the wear attributes of stir welded AA 7075 and A384 (Both in T6 condition). Experimentation revealed that higher order of wear is observed for A384 T6 and lower trend is observed for the later.…”
Section: Introductionmentioning
confidence: 99%
“…Such alloys are used in various components of aerospace applications. 22,23 However, a lack of examination and improvement during the TE experiments of aluminum alloys is observed. This study aims at examining the effect of the annealing temperature on the TE behavior of aluminum alloy AA 7075, as indicated by the post-processing mechanical properties, including the tensile strength, micro-hardness and microstructural characteristics.…”
Section: Introductionmentioning
confidence: 99%